ADVANCES IN TREATMENT OF MOOD DISORDERS - Shah, Asim A. (Journal of Pakistan Psychiatric Society, 2022)
In the last many decades psychotropics have mostly focused on Serotonin, Norepinephrine, and Dopamine for depression, and dopamine blockers for psychosis. Researchers started working diligently and explored new targets like Glutamate in treating depressive disorder and schizophrenia. The antagonist effect of Ketamine on N-methyl-D-aspartate (NMDA) receptors was investigated, which can result in a faster antidepressant response as compared to conventional treatment . GABA receptors were also explored to develop novel compounds, which resulted in the discovery of brexanalone, a neuroactive steroid-positive allosteric modulator of GABAA   approved in March 2019 by the FDA for the treatment of postpartum depression. It is administered as an intravenous infusion over 60 hours and results in a rapid antidepressant response in` postpartum depression lasting for more than one week. Another neuroactive steroid Zuranolone effectively treats postpartum depression and major depressive disorder (MDD) . The antidepressant also modulates neuronal plasticity by enhancing the Brain-derived neurotropic factor BDNF levels.